Barriers in financing microenterprises from the perspective of Czech and Slovak microentrepreneurs - Civelek, Mehmet; Ključnikov, Aleksandr; Krištofík, Peter; Rozsa, Zoltán (Journal of Business Economics and Management, 2019)
This paper compares how Czech and Slovak microentrepreneurs perceive the volume and ease of access to finance that they face. Having an adequate number of sources of finance and easier access to them can help improve both enterprise and country performance. Chi-square and Z score tests for population proportions were used to test hypotheses. 740 microenterprises from Czech Republic and 287 microenterprises from Slovakia were included for the analyses that were performed by this study. The results show that Czech microentrepreneurs feel they have more sources of finance and have easier access to them than their Slovak counterparts. These differences may in part be linked to other factors such as the experience and age of microentrepreneurs and micro-firms, amount of business loans and microfinancing organizations, credit interest rates and credit rejection rates, the relative degree of economic freedom, the volume of government guarantees, relative GDP levels, the quality of business environment and ease of doing business. Additionally, The Moran’s I spatial autocorrelation index was performed to evaluate influence of location on the perception of Czech and Slovak microenterprises that were located in different regions of both countries. The paper also discusses the results’ policy implications for governments and financial institutions.